2022
DOI: 10.3389/fped.2022.1050023
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Allan-Herndon-Dudley Syndrome in Chinese children: Identification of two novel pathogenic variants of the SLC16A2 gene

Abstract: ObjectiveThe aim of this study was to identify causative variants associated with Allan-Herndon-Dudley syndrome (AHDS) in two unrelated Chinese families, and to determine their potential pathogenicity. We also summarized the core clinical symptoms of AHDS by reviewing the related literature.MethodsGenomic DNA was isolated from the peripheral blood of AHDS patients and their family members. Whole exome sequencing (WES) was performed on the proband from each family to identify the candidate variants. Subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Due to the absence of systematic epidemiologic investigations, the precise prevalence of AHDS remains unknown [2] although it is believed to affect <1 in 1,000,000 individuals, predominantly males. [8] A study by Li et al, utilizing exome sequencing in children diagnosed with "cerebral palsy," identified the SLC16A2 variant, [10] suggesting potential cases of AHDS disguised as cerebral palsy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the absence of systematic epidemiologic investigations, the precise prevalence of AHDS remains unknown [2] although it is believed to affect <1 in 1,000,000 individuals, predominantly males. [8] A study by Li et al, utilizing exome sequencing in children diagnosed with "cerebral palsy," identified the SLC16A2 variant, [10] suggesting potential cases of AHDS disguised as cerebral palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, considering the number of reported cases in the literature, we hypothesized that this syndrome may be more common than previously thought. [2] MCT8 has been identified as a specific active transporter for TH, which is crucial for T3 transport across the blood-brain barrier and T3 uptake into neuronal cells. [11] Impaired thyroid hormone transport through the central nervous system during critical developmental stages, particularly in the first 2 years of life, can severely disrupt developmental processes and myelination, [9] leading to neurological deficits such as mental retardation, dystonia, spastic paraplegia, central hypotonia, and delayed verbal development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, the RNA sequencing of cerebral and striatal tissues of postnatal DKO mice revealed a significant number of dysregulated genes that do not overlap with those seen in mice, which were rendered systemically hypothyroid by an anti-thyroid drug treatment [16]. Likewise, the clinical profile of AHDS does not fully recapitulate that of patients with neurological cretinism, which is caused by a lack of TH supply during prenatal stages [17]. It is therefore reasonable to assume that specific brain regions and/or cell types rely, to a different extent, on MCT8-mediated TH transport and that other, yet unknown TH transporters may be able to compensate for the absence of MCT8 in certain cell types and developmental stages [5].…”
Section: Introductionmentioning
confidence: 99%